A preoperative risk scoring system for survival prediction in clinical stage IB lung adenocarcinoma: a multicenter study - Murakami, Kotaro; Isaka, Tetsuya; Nagashima, Takuya; Adachi, Hiroyuki; Shigefuku, Shunsuke; Kikunishi, Noritake; Shigeta, Naoko; Kudo, Yujin; Miyata, Yoshihiro; Okada, Morihito; Ikeda, Norihiko; Ito, Hiroyuki (Frontiers in Oncology, 2026)
BackgroundClinical stage (c-stage) IB lung adenocarcinoma (LUAD) presents variable survival outcomes, and the prognostic significance of factors such as ground-glass opacity components and positron emission tomography (PET) metrics remains unclear. Despite recent advances, no preoperative scoring model has been established to stratify risk in this subgroup. We aimed to identify preoperative prognostic factors in c-stage IB LUAD and develop a simple scoring system for predicting overall survival (OS).MethodsWe retrospectively analyzed data from 245 patients with c-stage IB LUAD who underwent lobectomy at three institutions between 2010 and 2020. Cox regression analysis was performed to identify independent preoperative prognostic factors for OS. A risk score was developed by assigning points to each factor, based on the regression coefficients. Thereafter, patients were stratified into four risk groups based on their total scores.ResultsMultivariate analysis identified smoking history (hazard ratio [HR]: 2.68; 95% confidence interval [CI]: 1.13–6.33; p=0.025), elevated serum carcinoembryonic antigen (CEA) levels (HR: 2.89; 95%CI: 1.42–5.91; p=0.004), and high maximum standardized uptake value (SUVmax) on PET (HR: 2.84; 95%CI: 1.16–6.98; p=0.023) as independent factors of poor prognosis. A scoring system was established by assigning one point to each factor. Patients were stratified into four risk groups: low (score 0, n=41), moderate (score 1, n=84), moderately high (score 2, n=77), and extremely high (score 3, n=43). Five-year OS rates were 100.0%, 89.3%, 74.0%, and 52.1%, respectively (p<0.001). The prognostic model demonstrated acceptable discrimination ability, with an area under the curve of 0.738 (95% CI, 0.661–0.815) and a concordance index of 0.753 (95% CI, 0.682–0.824). Notably, patients with a score of 0 showed low-grade tumors and favorable prognosis, whereas those with a score of 3 had more aggressive pathological characteristics and significantly worse outcomes.ConclusionsWe developed and validated a simple preoperative scoring system using smoking history, serum CEA level, and tumor SUVmax to predict prognosis in c-stage IB LUAD. This model provides a practical tool for risk stratification and may support individualized treatment decisions, including the consideration of induction therapy in selected cases.